Activated protein C does not increase in the early phase of trauma with disseminated intravascular coagulation: comparison with acute coagulopathy of trauma-shock. Issue 1 (December 2016) - Jesmin, Subrina; Gando, Satoshi; Wada, Takeshi; Hayakawa, Mineji; Sawamura, Atsushi
Abstract We hypothesized that activated protein C does not increase in disseminated intravascular coagulation (DIC) after trauma and that the same is true for acute coagulopathy of trauma-shock (ACOTS). Activated protein C levels were prospectively measured in 57 trauma patients: 30 with DIC and 27 without DIC. Normal to more decreased activated protein C levels were observed in DIC patients than in the controls and non-DIC patients. The activated protein C levels in ACOTS patients were similar to those in DIC patients. In conclusion, activated protein C does not increase in either DIC or ACOTS in the early phase of trauma.